Estimation of direct economic and productive losses due to abortions caused by Neospora caninum in the primary dairy sector of Uruguay - Carrillo Parraguez, Miguel; Ponssa, Eduardo; Caffarena, Darío; Artagaveytia, Jorge; Sotelo, Fernando; Fariña, Santiago; Mendoza, Alejandro; Giannitti, Federico (Frontiers in Veterinary Science, 2025)
Despite its sociocultural and economic importance, dairy farming in Uruguay has not experienced a significant increase in cattle stocks in recent decades, partly due to low reproductive efficiency and a high risk of calf mortality. Neospora caninum is one of the primary abortive pathogens in dairy cattle; however, the economic losses caused by neosporosis in Uruguay remain uncalculated. This study aimed to assess the direct annual economic losses for the primary dairy sector (dairy farmers) due to abortions resulting from bovine neosporosis in the Uruguayan herd. An adjusted bioeconomic model was used to estimate the economic losses from early (second gestational trimester) or late (third gestational trimester) abortions, considering the Present Value (PV) of future production loss due to these abortions after deducting production costs (lost profits). The average economic loss per abortion due to neosporosis was US$ 868 (range 605–1,162) if the aborting cow remained in the herd without any additional abortions throughout its productive life and US$ 1,866 (range 782–2,825) if the cow was culled after the abortion. Individual losses varied based on the gestational stage and the age of the aborting cow, with the worst-case scenario being a late abortion in first-pregnancy heifers. The annual number of abortions due to neosporosis was estimated by considering the stock of cows and heifers of reproductive age at risk of abortion (pregnant) and the national seroprevalence of N. caninum in dairy herds, accounting for 90% vertical transmission and 10% horizontal transmission, with aborting seropositive dams representing 15 and 35%, respectively. The economic losses for the national herd were calculated by multiplying individual losses by the number of abortions across various simulated scenarios (second or third gestational trimester), adjusted according to sub-scenarios (with and without culling of the aborted cow). The estimated economic losses for the primary sector due to abortions occurring in 2018 totaled nearly US$ 12 million, which is attributed to the loss of offspring, delayed lactation, reduced productive life (fewer days in milk production/days of life), and early culling. These estimated losses reflect only the primary sector, excluding the secondary (industrial) and tertiary (services) sectors. In physical terms, abortions associated with neosporosis caused a total loss of 62 million L of milk, which is 3.3% of the volume industrialized annually in the country. The estimated losses did not account for profits lost by dairy farmers from beef production (i.e., breeding, fattening, and sale for slaughter of male calves from dairy breeds lost due to neosporosis) nor any indirect losses (for example, the loss of genetic merit, stunted growth of the national dairy stock, etc.). The characteristics of Uruguay’s grazing dairy production system require a tailored approach to estimating the economic impact of bovine diseases. This information can be used by farmers, veterinarians, and policymakers to evaluate the cost–benefit of implementing control and prevention strategies for bovine neosporosis at both the farm and national levels.